Pembentukan Ad Divergence Pada Iklan Kreatif Kredivo Versi #Sefleksibelitu - Qoyyum, Arfi Ma’rufi (CITRAWIRA : Journal of Advertising and Visual Communication, 2022)
Creative advertising raises interesting points inherent in the ad itself. This is because the concept of divergent thinking is adapted and developed in advertising science with 5 main dimensions, namely originality, flexibility, elaboration, synthesis, and artistic value, which is commonly called Ad Divergence by Robert E Smith from Torrance Test of Creative Thinking and Guildford Theory on creativity. This research method uses descriptive qualitative, namely by collecting data through observation, documentation, and literature study. Research on the formation of Ad Divergence in Kredivo's Creative Ads Version #Seflexbel is to find and identify the application of Ad Divergence in Kredivo's fintech product advertisements. The results of the study show that there is the formation of each dimension of Ad Divergence, but only 2 dimensions dominate the application in the ad.